The Influence of Brand Equity and Halal Labels on Purchase Intention from an Islamic Marketing Perspective - Putri Intan Purnama; Afif Zaerofi (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2026)
Purpose – This study aims to analyze the effect of brand equity and halal labels on purchase intention toward Wardah cosmetics from an Islamic marketing perspective in the Bogor region. It builds on previous studies that show inconsistent results regarding the role of halal attributes in consumer purchase behavior. By incorporating halal awareness as a moderating variable and applying the SEM-PLS method, this study seeks to clarify these relationships in a local halal cosmetics market. The findings indicate that brand equity and brand image positively influence purchase intention, while halal awareness does not moderate these effects. Design/Methods/Approach – This study employed a quantitative approach using a survey method to collect data from consumers who have purchased Wardah cosmetics in the Bogor region. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships between brand equity, brand image, halal awareness, and purchase intention. Findings – The results show that brand equity and brand image have a positive and significant effect on purchase intention. However, halal awareness does not moderate the relationship between brand equity and purchase intention, nor between brand image and purchase intention. These findings indicate that branding factors play a more dominant role than halal awareness in influencing consumers’ purchase intention toward Wardah cosmetics in the Bogor region. Research Implications/Limitations – This study is limited by its focus on a single halal cosmetic brand (Wardah) and a specific geographic area (Bogor), which may restrict the generalizability of the findings to other brands or regions. The use of a cross-sectional survey and self-reported data may also limit the ability to capture changes in consumer behavior over time. Nevertheless, the findings provide practical implications for halal cosmetic marketers by highlighting the greater importance of brand equity and brand image compared to halal awareness in shaping purchase intention within a local Muslim market. Originality/Value – This study adds value to Islamic marketing literature by providing empirical evidence on the relative influence of branding factors and halal awareness on purchase intention in a local halal cosmetics market. By incorporating halal awareness as a moderating variable and focusing on Wardah consumers in Bogor, this research offers a contextual contribution that complements prior studies with mixed findings. Future research may extend this model to different brands, regions, or longitudinal designs to enhance generalizability.